2006
DOI: 10.1007/s00003-006-0036-z
|View full text |Cite
|
Sign up to set email alerts
|

Animal Feed Production and Contamination by Foodborne Salmonella

Abstract: Animal feeds can

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 181 publications
(224 reference statements)
0
34
0
1
Order By: Relevance
“…Animal feed is a recognized source of pathogenic microorganisms for animals [16]. It is still relatively common to find evidence of contamination of domestic and imported feed and animal-feed ingredients [17][18][19][20][21][22][23][24][25][26]. Salmonella can be isolated regularly from feedstuffs and feed ingredients, including both animal and vegetable proteins, such as soya, rape, palm kernel, rice bran and cottonseed.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…Animal feed is a recognized source of pathogenic microorganisms for animals [16]. It is still relatively common to find evidence of contamination of domestic and imported feed and animal-feed ingredients [17][18][19][20][21][22][23][24][25][26]. Salmonella can be isolated regularly from feedstuffs and feed ingredients, including both animal and vegetable proteins, such as soya, rape, palm kernel, rice bran and cottonseed.…”
Section: Results and Disscusionmentioning
confidence: 99%
“…The viability of food borne illnesses, such as Salmonella sp . have likewise been studied in feed and feed ingredients [11]. Based on the fact that ingredient processing procedures can successfully render PEDV inactive [12], this study operated under the premise of post-processing contamination of all ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, research has aimed to develop alternative methods for molting, new procedures that would avoid feed removal, but retain at the same time the economic benefits (Maciorowski and others ). For molting purposes, Woodward and others () demonstrated that alfalfa could be used as an alternative, resulting in a reduction of S .…”
Section: Preharvest Methods For Reducing the Risk Of Salmonella Contamentioning
confidence: 99%
“…Different protein sources and cereals have been identified as contaminated with Salmonella spp. : peanut meal, sunflower meal, soybean meal, bran meal, barley, corn, sorghum, and wheat (Maciorowski and others ). Sunflower yielded the highest number of positive samples for Salmonella spp.…”
Section: Preharvest Methods For Reducing the Risk Of Salmonella Contamentioning
confidence: 99%